Lignin-Based Adsorbent Materials for Metal Ion Removal from Wastewater: A Review - Sanchez-Poblete, J; Yanez-Sanchez, M; Santander-Meyer, R; Oyarce-Riveros, E (Elsevier B.V., 2021)
Water is essential for the development of life on earth; therefore, its decontamination is essential. Among the pollutants that threaten this water resources are metal ions, since they are considered highly toxic and carcinogenic. In recent years, the use of biodegradable raw materials for the development of new adsorbent materials has generated great attention for being environmentally friendly materials. Lignin is an amorphous biopolymer and one of the most abundant on the planet. It has carboxyl groups and phenolic units in its macromolecular structure, capable of interacting with metal ions. Lignin can be chemically and physically modified to obtain new materials with improved properties. For this reason, this article provides a comprehensive review of the latest research on heavy metal ion removal using lignin-based adsorbent materials. This review considers the mechanisms to obtain the lignin-based materials, the metal removal efficiency and the adsorption capacity. Likewise, the methods for incorporating oxygen, nitrogen and sulfur into the biopolymeric structure, the formation of lignin nanoparticles, composites, lignin-based hydrogels and lignin-based biochars were also reviewed. © 2021 Elsevier B.V.